Restricted distribution and lateralization of mutualistic Wolbachia in the Drosophila brain. (22nd July 2016) - Strunov, Anton; Schneider, Daniela I.; Albertson, Roger; Miller, Wolfgang J.
Summary: Microbial symbionts are universal entities of all living organisms that can significantly affect host fitness traits in manifold ways but, even more fascinating, also their behaviour. Although better known from parasitic symbionts, we currently lack any cases where 'neurotrophic' symbionts have co‐evolved mutualistic behavioural interactions from which both partners profit. By theory, most mutualistic associations have originated from ancestral parasitic ones during their long‐term co‐evolution towards a cost–benefit equilibrium. To manipulate host behaviour in a way where both partners benefit in a reciprocal manner, the symbiont has to target and remain restricted to defined host brain regions to minimize unnecessary fitness costs. By using the classic Drosophila paulistorum model system we demonstrate that ( i ) mutualistic Wolbachia are restricted to various Drosophila brain areas, ( ii ) form bacteriocyte‐like structures within the brain, ( iii ) exhibit strictly lateral tropism, and ( iv ) finally propose that their selective neuronal infection affects host sexual behaviour adaptively.